Back squat vs. hip thrust resistance-training programs in well-trained women - Barbalho, M.; Coswig, V.; Souza, D.; Serrao, J. C.; Hebling Campos, M.; Gentil, P. (International Journal of Sports Medicine, 2020)
The study compared the effects of back squat (BS) and hip thrust (HT) exercises on muscle strength and hypertrophy in well-trained women. Twenty-two participants were divided in two groups: BS group (n=12, 26.4±1.32 years, 171.8±3.79 cm, and 69.5±4.9 kg) performed the BS exercise and HT group (n=10, 27.5±1.42 years, 170.8±4.4 cm, 67.5±4.7 kg) performed the HT exercise. Training was performed for 12 weeks. Before and after the training period, participants were assessed for quadriceps femoris and gluteus maximus muscle thickness (MT) and 1 repetition maximum (1RM) test on the BS and HT. Both groups significantly increased hip extensors MT and HT 1RM; however, the improvements in BS group were higher than in HT group on quadriceps femoris (12.2% for BS and 2% for HT, P<0.001) and gluteus maximus MT (9.4% for BS and 3.7% for HT, P=0.001) and BS 1 RM (35.9% for BS and 4.3% for HT, P<0.001). BS was more efficient than HT, since it resulted in greater muscle hypertrophy of the quadriceps femoris and gluteus maximus, increases in BS 1RM and similar increases in HT.